SPILLOVER VOLATILITAS HARGA MINYAK DUNIA PADA PASAR MODAL INDONESIA PERIODE TAHUN 2017-2022 - Tyas Danarti Hascaryani; Adam Zain (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
World crude oil prices as represented by Brent Crude and West Texas Intermediate (WTI) have decreased in line with the decline in the Indonesia Composite Index (ICI) during the Covid-19 outbreak. Many countries implemented lockdown policies during the Covid-19 period, thereby hampering the pace of Indonesia's economy as a crude oil importing country. Therefore, this study aims to explain the difference in volatility spillover from world crude oil in ICI